Feasibility of Thrombectomy in Treating Acute Ischemic Stroke Because of Cervical Artery Dissection. Issue 12 (December 2018) - Li, Shun; Zi, Wenjie; Chen, Jingjing; Zhang, Shuai; Bai, Yongjie; Guo, Yongtao; Shang, Xianjin; Sun, Bo; Liang, Meng; Liu, Yong; Wan, Yue; Wang, Mengmeng; et al.
Abstract : Background and Purpose—: Acute ischemic stroke caused by cervical artery dissection tend to result in unfavorable outcomes even with appropriate medical treatment. This study evaluated the safety and effectiveness of endovascular thrombectomy in treating acute ischemic stroke associated with cervical artery dissection. Methods—: Patients with acute ischemic stroke and with large artery occlusion associated with dissection were selected. Propensity score matching was performed to increase the comparability. Patients with a 90-day modified Rankin Scale score of 0 to 2 were defined as with favorable outcome. Results—: Eighty patients with and 80 patients without thrombectomy were enrolled. After propensity score matching, 48 patients with and 48 patients without thrombectomy were matched for further analysis. Proportion of favorable outcome (modified Rankin Scale score of 0–2) was higher in patients with thrombectomy than in those without (66.7% versus 39.6%; P =0.008). There were no significance differences about the incidence of symptomatic intracranial hemorrhage (8.3% versus 4.2%; P =0.677) and the 90-day mortality (10.4% versus 6.3%; P =0.714) between matched patients with and without thrombectomy. Conclusions—: Endovascular thrombectomy seems to be an effective treatment in selected patients with acute ischemic stroke associated with cervical artery dissection, but the safety of thrombectomy needs further research. Abstract : Supplemental Digital Content is available in the text.